Implementing an information system development simulation in an industrial engineering class: A case study - Sakgasit Ramingwong (2018)
© Springer-Verlag Berlin Heidelberg 2015. Development of an information system is a challenging task due to many of its unique and sensitive nature. As stakeholders, it is important for both managerial and technical counterparts to understand the challenges in information system development. This paper explores the efficiency of implementing a simulation workshop on information system development in an industrial engineering class as well as report lesson leant from the industrial points of view.